Stable positioning of Unc13 restricts synaptic vesicle fusion to defined release sites to promote synchronous neurotransmission - Reddy Alla, Suneel; Hell, Stefan (Neuron, 2017)
Summary Neural information processing depends on precisely timed, Ca2+-activated synaptic vesicle exocytosis from release sites within active zones (AZs), but molecular details are unknown. Here, we identify that the (M)Unc13-family member Unc13A generates release sites and show the physiological relevance of their restrictive AZ targeting. Super-resolution and intravital imaging of Drosophila neuromuscular junctions revealed that (unlike the other release factors Unc18 and Syntaxin-1A) Unc13A was stably and precisely positioned at AZs. Local Unc13A levels predicted single AZ activity. Different Unc13A portions selectively affected release site number, position, and functionality. An N-terminal fragment stably localized to AZs, displaced endogenous Unc13A, and reduced the number of release sites, while a C-terminal fragment generated excessive sites at atypical locations, resulting in reduced and delayed evoked transmission that displayed excessive facilitation. Thus, release site generation by the Unc13A C terminus and their specific AZ localization via the N terminus ensure efficient transmission and prevent ectopic, temporally imprecise release.
Gesehen am 25.10.2018